FT-IR spectroscopic investigation of adsorption of 3-aminopyridine on sepiolite and montmorillonite from Anatolia - Yakar, A. E.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Elsevier, 2001)
The adsorption of 3-aminopyridine by natural sepiolite and montmorillonite from Eskisehir (Anatolia) was investigated in the temperature range from 20 to 125°C by infrared spectrometry using a variable temperature unit. The spectroscopic results indicate that the 3-aminopyridine molecules adsorbed on sepiolite are coordinated to Lewis acidic sites and/or surface hydroxyls by H-bonding interaction through pyridine ring nitrogen lone pairs. Surface Bronsted acid strength of sepiolite is weak and 3-aminopyridinium is not detected under the conditions applied in this study. It must be noted that the adsorption of aminopyridine affected the hydroxyl group vibrations of sepiolite. The intercalation of 3-aminopyridine within montmorillonite has been shown by X-ray diffraction to increase the interlayer spacing. IR spectroscopy indicates that sorbed 3-aminopyridine molecules by montmorillonite are mostly coordinated to exchangeable cations directly or indirectly through water bridges. The formation of 3-aminopyridinium cation is also detected at elevated temperatures.
Keywords: FT-IR; Aminopyridine; Adsorption; Intercalation; Sepiolite; Montmorillonite